The financial performance of plantation companies in Malaysia / Noraini Mohd Yussof - Mohd Yussof, Noraini (2012)
The plantations industry has become an important sector to both developed and developing country, including Malaysia. Acknowledging positive advantages of plantation, much research has been carried out on business in plantation industry. In this paper, an attempt is made to know the financial performance of selected plantation companies, for accomplishment of the objective, the data collected from the financial information that are get from DataStream for year 2002-2011 from the selected 26 plantation companies in Malaysia, and then the collected data is analyzed and computed to meet the objectives of the study.